2021
DOI: 10.1159/000517462
|View full text |Cite
|
Sign up to set email alerts
|

Transporters, <b><i>TBC1D4</i></b>, and <b><i>ARID5B</i></b> Variants to Explain Glycated Hemoglobin Variability in Patients with Type 2 Diabetes

Abstract: <b><i>Introduction:</i></b> Genetic variants could aid in predicting antidiabetic drug response by associating them with markers of glucose control, such as glycated hemoglobin (HbA1c). However, pharmacogenetic implementation for antidiabetics is still under development, as the list of actionable markers is being populated and validated. This study explores potential associations between genetic variants and plasma levels of HbA1c in 100 patients under treatment with metformin. <b>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…At present, it is mainly used in the diagnosis and prognosis evaluation of left ventricular dysfunction [ 31 ]. The results showed that the level of brain natriuretic peptide in acute exacerbation and remission stage of cor pulmonale was higher than that in the control group, suggesting that brain natriuretic peptide was also involved in the pathophysiological process of right ventricular changes in cor pulmonale [ 32 ]. The level of brain natriuretic peptide in acute exacerbation stage was the highest but decreased in remission stage, but it was still higher than that in the control group, suggesting that brain natriuretic peptide can be used as one of the indicators to judge the severity of pulmonary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is mainly used in the diagnosis and prognosis evaluation of left ventricular dysfunction [ 31 ]. The results showed that the level of brain natriuretic peptide in acute exacerbation and remission stage of cor pulmonale was higher than that in the control group, suggesting that brain natriuretic peptide was also involved in the pathophysiological process of right ventricular changes in cor pulmonale [ 32 ]. The level of brain natriuretic peptide in acute exacerbation stage was the highest but decreased in remission stage, but it was still higher than that in the control group, suggesting that brain natriuretic peptide can be used as one of the indicators to judge the severity of pulmonary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…HbA1c serves as the primary criterion for diagnosing diabetes and prediabetes [30]. However, the HbA1c level measured by the analyzer reflects only 60-80% of the average blood glucose level, and the remaining 20-40% of HbA1c variation may not be accounted for by the observed HbA1c values [31][32][33]. To provide a comprehensive reflection of the blood glucose metabolic state, Hempe et al proposed HGI, which quantifies interindividual variations in HbA1c resulting from factors beyond blood glucose concentration [34].…”
Section: Discussionmentioning
confidence: 99%
“…Variants associated with the highest values of age- and sex-specific insulin showed associations with above-median values of log-insulin but not with values below the median, and were often located in genes that had been found to be related to type 2 diabetes in previous studies. For instance, a variant associated with the 85th percentile of z -insulin was located on the SLC28A1 (or CNT1 ) gene that has been linked to type 2 diabetes [ 26 ]. Two variants associated with the 15th percentile of z -insulin were located on genes previously linked with insulin secretion and beta cell function ( RBFOX1 ) [ 27 ] and measures of insulin resistance ( SH3RF3 ) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent findings of an association between diabetes and dementia prompted researchers to investigate the shared genetic architecture between metabolic traits and Alzheimer’s disease [ 35 ] and other neuropsychiatric disorders [ 36 ]. The present study showed that a variant associated with the high end of the z -insulin spectrum (rs2122859) was located on the SLC28A1 gene, which has been shown to be associated with both diabetes [ 26 ] and late-onset Alzheimer’s disease [ 37 ]. Interestingly, two variants associated with low z -insulin in the present study were located on RBFOX1 and SH3RF3 , genes that have previously been shown to be related to brain amyloidosis in preclinical Alzheimer’s disease [ 38 ] and to late-onset Alzheimer’s disease [ 39 ], respectively.…”
Section: Discussionmentioning
confidence: 99%